Analysis of food and biological value of fish processing waste - Дуденко, Ніна Василівна; Панікарова, Богдана Олександрівна; Горбань, Віктор Григорович (Technology audit and production reserves, 2015)
The prospects and necessity of involving the fish protein-containing waste in the production cycle of food production is proved in the article. The main aim is research and evaluation of food and biological value of fish waste generated as a result of production of semi-finished goods or stuffing. These data show that most perspective protein-containing waste is a fish skin, because it is rich in protein and fat, as well as some amino acids specific for collagen. It is found that the amino acid composition of fish skins is defective, however, it can be easily balanced by binding to muscle tissue. We propose to use fish skin in meat systems after appropriate processing to impart plasticity and softness.